Active nitrogen fixation by Crocosphaera expands their niche despite the presence of ammonium - A case study - Inomura, Keisuke; Masuda, Takako; Gauglitz, Julia M (Scientific reports, 2019)
Unicellular nitrogen fixer Crocosphaera contributes substantially to nitrogen fixation in oligotrophic subtropical gyres. They fix nitrogen even when significant amounts of ammonium are available. This has been puzzling since fixing nitrogen is energetically inefficient compared with using available ammonium. Here we show that by fixing nitrogen, Crocosphaera can increase their population and expand their niche despite the presence of ammonium. We have developed a simple but mechanistic model of Crocosphaera based on their growth in steady state culture. The model shows that the growth of Crocosphaera can become nitrogen limited despite their capability to fix nitrogen. When they fix nitrogen, the population increases by up to 78% relative to the case without nitrogen fixation. When we simulate a simple ecological situation where Crocosphaera exists with non-nitrogen-fixing phytoplankton, the relative abundance of Crocosphaera increases with nitrogen fixation, while the population of non-nitrogen-fixing phytoplankton decreases since a larger fraction of fixed nitrogen is consumed by Crocosphaera. Our study quantitatively supports the benefit of nitrogen fixation despite the high electron/energy costs, even when an energetically efficient alternative is available. It demonstrates a competitive aspect of Crocosphaera, permitting them to be regionally significant nitrogen fixers.
Keywords: biologické modely; fytoplankton; dusík; Carbon; amoniové sloučeniny; Cyanobacteria; Models, Biological; Nitrogen Fixation; Phytoplankton; Ammonium Compounds; Phosphorus; fosfor; sinice; Computer Simulation; uhlík; Nitrogen; fixace dusíku; počítačová simulace